Mortality and clinical outcomes of colistin versus colistin-based combination therapy for infections caused by Multidrug-resistant Acinetobacter baumannii in critically ill patients - Marwan J. Alwazzeh; Jumanah Algazaq; Fatimah Ali Al-Salem; Fatimah Alabkari; Sara M. Alwarthan; Mashael Alhajri; Bashayer M. AlShehail; Amani Alnimr; Ahmad Wajeeh Alrefaai; Faten Hussain Alsaihati; Fahd Abdulaziz Almuhanna (BMC Infectious Diseases)
Abstract Background Multidrug-resistant Acinetobacter baumannii emerged as a threatening “superbug” with significant morbidity and mortality and limited antimicrobial therapy options. The results of different antibiotic combination studies are heterogeneous and controversial. Further comparative studies are crucial to overcome such difficult-to-treat infections and to improve patient outcomes. This study investigates the mortality and outcomes of colistin versus colistin-based combination therapy for infections caused by Multidrug-resistant Acinetobacter baumannii in critically ill patients. Methods A retrospective observational study was conducted at an academic tertiary hospital in Khobar City, Eastern Province, Saudi Arabia. Patients who fulfilled the inclusion criteria and were admitted from January 1, 2017, to December 31, 2022, were included. The investigated primary outcome was 30-day mortality, while secondary outcomes were one-year all-cause mortality, clinical cure, microbiologic eradication, and recurrence of Acinetobacter infections. Statistical comparisons were employed, and a P-value of ≤ .05 was considered significant. Results Of the 178 patients who fulfilled the inclusion criteria, 47 received colistin only, and 131 received colistin in combinations (55 with carbapenems, 53 with tigecycline, and 23 with both). The estimated 30-day mortality rate of the study population was 22.5%, with statistically insignificant differences in 30-day mortality rates when the colistin group compared to cumulative colistin-based combination (23.4% vs. 22.1%; difference, 1.3 percentage points; 95% confidence interval [CI], 0.487–2.371; P = 0.858) or subgroups. However, colistin-based combination groups showed better secondary outcomes, with significantly less all-cause mortality and better clinical cure in colistin combination with carbapenems or tigecycline and less Acinetobacter infection recurrence in combination with carbapenems. Conclusions The study findings demonstrate the benefits of investigated colistin combination options that result in less one-year all-cause mortality, better clinical cure, higher microbiologic response, and less infection recurrence. However, no significant differences were observed regarding 30-day mortality. In addition, the study highlights the limitations of the available antimicrobial options and the crucial need for new effective antimicrobials and more successful combinations.